2005
DOI: 10.1038/nature03483
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of kinetochore capture by spindle microtubules

Abstract: For high-fidelity chromosome segregation, kinetochores must be properly captured by spindle microtubules, but the mechanisms underlying initial kinetochore capture have remained elusive. Here we visualized individual kinetochore-microtubule interactions in Saccharomyces cerevisiae by regulating the activity of a centromere. Kinetochores are captured by the side of microtubules extending from spindle poles, and are subsequently transported poleward along them. The microtubule extension from spindle poles requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
387
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(419 citation statements)
references
References 49 publications
30
387
2
Order By: Relevance
“…The original search-and-capture model supposed that KC attachments to MTs are end-on, consistent with the results of Kalinina et al (24), while others observed primarily lateral attachments (14,19,20,23,25). Therefore, we studied how the probability of lateral or end-on attachment varied with MT length and the presence or absence of rotational diffusion in the model (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…The original search-and-capture model supposed that KC attachments to MTs are end-on, consistent with the results of Kalinina et al (24), while others observed primarily lateral attachments (14,19,20,23,25). Therefore, we studied how the probability of lateral or end-on attachment varied with MT length and the presence or absence of rotational diffusion in the model (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…In prometaphase, kinetochores, a protein structure formed at the centromere of each sister chromatid, 'capture' and interact with microtubules projecting from centrosomes (search and capture model) (Rieder and Salmon, 1998;Hayden et al, 1990;Tanaka et al, 2005;Tanaka et al, 2008). Kinetochores are then moved along the length of the attached microtubules toward the spindle pole promoted by kinetochore associated minus-end motor proteins (dynein in metazoans and kinesin-14 in budding yeast) (Rieder and Alexander, 1990;Yang et al, 2007b;King et al, 2000;Tanaka et al, 2007).…”
Section: Centrosome Sister Chromatidmentioning
confidence: 99%
“…We were not able to analyze the main-tenance of a previously assembled kinetochore because cells needed to pass through S phase to deplete Cse4 from the eCEN. Because kinetochores likely disassemble during S phase (Tanaka et al, 2005), studies at the eCEN would not distinguish between kinetochore assembly and maintenance. All proteins tested exhibited some dependence on Cse4 for localization to the cCEN.…”
Section: The Functions Of Cenh3mentioning
confidence: 99%
“…When cells are grown in galactose media, transcription through the cCEN keeps it inactive. The addition of glucose represses transcription at the cCEN, allowing a functional kinetochore to form within 20 min (Hill and Bloom, 1989;Neff and Burke, 1992;Dewar et al, 2004;Tanaka et al, 2005).To begin analyzing the cell cycle restrictions over kinetochore assembly, we first determined whether kinetochores could assemble in G 1 cells. Kinetochore assembly at the cCEN was analyzed using ChIP.…”
mentioning
confidence: 99%